2015
DOI: 10.35188/unu-wider/2015/925-1
|View full text |Cite
|
Sign up to set email alerts
|

Income mobility in Ecuador: New evidence from individual income tax returns

Abstract: This paper presents new evidence on the study of income mobility in Ecuador over the period 2004-11. We utilize longitudinal data of individual income tax returns to measure income mobility both at the top and at the middle of the income distribution, and we find three main empirical results. First, income mobility in Ecuador is low for top incomes: the probability of remaining in the top 1 per cent after one year is nearly 66 per cent, and it remains stable by the end of the period. Second, there is a high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(43 reference statements)
0
9
0
1
Order By: Relevance
“…In addition the authors found low intra-generational social mobility which they explain by the presence of poverty traps produced by lack of human and physical capital (Azevedo & Bouillon, 2009). In the case of Ecuador, Cano (2015) found that income mobility is low for top incomes, which may reflect structural inequalities, while education is a main driver of upward intragenerational mobility.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition the authors found low intra-generational social mobility which they explain by the presence of poverty traps produced by lack of human and physical capital (Azevedo & Bouillon, 2009). In the case of Ecuador, Cano (2015) found that income mobility is low for top incomes, which may reflect structural inequalities, while education is a main driver of upward intragenerational mobility.…”
Section: Empirical Evidencementioning
confidence: 99%
“…For a link between upward social mobility and overcoming chronic poverty see for example Carter & Barrett (2006. In this paper, we contribute by looking at social mobility not as a change in the income distribution (often called economic mobility), or education level and occupational status (often called social mobility) as is generally done in the literature (see for example Baulch & Hoddinott (2000), Woolard & Klasen (2005), Azevedo & Bouillon (2009), Crawford et al (2011), Sandberg (2012, Rodriguez-Oreggia & Freije (2012), Jäntti & Jenkins (2015), Lambert et al (2014), Cano (2015), but by considering a multidimensional welfare indicator reflecting the importance of different dimensions of structural poverty conditions (Carter & Barrett, 2006) and human development. Furthermore, by looking at intra-generational upward mobility we first analyse the extent to which households change their position in the welfare distribution over time, and the determinants that explain such movements.…”
Section: Introductionmentioning
confidence: 98%
“…On the other side, those that gave external researchers access to microdata at some point, but do not produce distributive information from tax registers on a regular basis (Colombia, Costa Rica and Ecuador). For these cases, we use estimates prepared by the authors of previous studies (Alvaredo and Londoño Velez, 2014;Cano, 2015;Zuniga-Cordero, 2018Rossignolo et al, 2016), which are restricted to the top percentile of the distribution only. In section A.2 we report the use of income tax data in the literature on top incomes for eight of our ten countries.…”
Section: Data Inputsmentioning
confidence: 99%
“…was able to calculate persistence rate for the top fractions of the population. In the context of the top incomes literature, only Cano (2015) was able to calculate persistence rate for the top fractions of the population.…”
Section: The Recent Evolution Of Top Income Shares In Latin Americamentioning
confidence: 99%